Invasive Lobular Carcinoma of the Breast with Extracellular Mucin: Case Report of a New Variant of Lobular Carcinoma of the Breast - M. Boukhechba; H. Kadiri; B. El Khannoussi (Hindawi Limited, 2018)
Invasive carcinoma of no special type (NST) or ductal carcinoma is the largest group of invasive breast cancers. Invasive lobular carcinoma (ILC) is the second most common histological type; it comprises 5%-15% of all invasive breast cancers. Historically, lobular neoplasia and invasive lobular carcinoma may produce intracellular mucin that pushes the nucleus to one side, creating the characteristic signet ring cell morphology. The extracellular mucin secretion is essentially described in mucinous breast carcinoma. Mucinous differentiation can be seen in small areas of NST carcinoma, but recently a few cases of invasive lobular carcinoma with extracellular mucin are reported in the literature. It is important for pathologists to recognize this new entity because it mimics a NST carcinoma, as such a diagnosis may require a different approach in clinical management and surveillance. We report a new case of ILC with extracellular mucin and a review of the literature.